First record of a highly melanic morph of Cyphostethus tristriatus (Fabricius, 1787) (Hemiptera: Heteroptera: Acanthosomatidae) - Taszakowski, Artur; Klejdysz, Tomasz; Gierlasiński, Grzegorz (Zootaxa, 2020)
The term ‘melanism’ means the occurrence of variant(s) that is/are mostly or completely dark in pigmentation either as intraspecific polymorphisms or as fixed differences between closely related species. Melanism can refer to variation involving discrete melanic and non-melanic phenotypes (melanic and typical morphs) or to cases of continuously varying pigmentation (True 2003). Melanism of moths inhabiting areas with industrial pollution is a very well-known example involving melanic polymorphisms in insects. However, melanism is also known in other insect orders, e.g. Coleoptera and Diptera (Majerus 1998, True 2003).